The Impact of Artisanal Gold Mining Activities in Ranggo Village, Ladore Sub-District, Pajo District, Dompu Regency, West Nusa Tenggara - Ari Aryansyah; Nurul Halizah; Yahdin Al Azhar; Bambang S Darusalam; Diah Rahmawati; Ariyanto Ariyanto (Jurnal Pertambangan dan Lingkungan, 2023)
Artisanal gold mining activities in Ranggo Village, Pajo District, Dompu Regency, have been going on since 2014 until today.  About 50% of the people who work as gold miners traditionally come from Ranggo Village, with an average of junior to senior high school graduates ranging from 20 to 40 years old and above.  This study aims to determine the social, economic and environmental impacts of traditional gold mining activities on the welfare of the community around the mine.  The method used for data collection was interviews, observation, and documentation.  The research results reveal a decrease in crime by 80 % due to the availability of jobs in gold mines operated by the community.  In addition, there is a significant increase in income of IDR 3,000,000 – IDR 5,000,000 every month.  However, the presence of artisanal gold mines in Ranggo Village raises environmental problems because the processing activities still use mercury.